Determination of the stochastic layer properties induced by magnetic perturbations via heat pulse experiments at ASDEX upgrade. (August 2017) - Brida, D.; Lunt, T.; Wischmeier, M.; Birkenmeier, G.; Cahyna, P.; Carralero, D.; Faitsch, M.; Feng, Y.; Kurzan, B.; Schubert, M.; Sieglin, B.; Suttrop, W.; et al.
Highlights: A new experimental method was applied in the tokamak ASDEX Upgrade to estimate the stochastic layer width of a deuterium L-mode discharge with Magnetic Perturbations. The findings indicate strong screening of the Magnetic Perturbations in this discharge. The effect of screening on the target fluxes was investigated numerically. For high densities no strong strike line splitting was found, independent of the screening degree. In an L-mode density ramp it was found that the strike line splitting vanishes completely for detached conditions. Abstract: A heat pulse experiment was carried out in the tokamak ASDEX Upgrade to estimate the stochastic layer width of a deuterium L-mode discharge with externally applied Magnetic Perturbations. The method relies on the deposition of ECRH pulses in the plasma edge while measuring the divertor target heat flux with high temporal resolution IR thermography and Langmuir probes. The experimental results were compared to simulations of the time dependent heat pulse propagation on a constant plasma background with the EMC3-EIRENE code package, using an ad-hoc screening model. If no screening was taken into account in the simulations a decrease in the characteristic heat pulse propagation time was observed, which shows that the heat transport is enhanced compared to the screened cases. No such enhancement was found in the experiment, indicating strong screening. In further simulations the effect of screening on the target fluxes was investigated for varying densities. For low densities it was found that screening reduces the strike line splitting strongly, while for higher densities no strong strike line splitting was found, independent of the screening degree. For strongly detached L-mode conditions with MPs experiments at AUG indicate that the lobe structures vanish completely.